Biodegradation of Bis-Azo Dye Reactive Black 5 byWhite-Rot Fungus Trametes gibbosa sp. WRF 3 and Its Metabolite Characterization - Liyana Amalina Binti Adnan; Abdull Rahim Mohd Yusoff; Tony Hadibarata; Ameer Badr Khudhair (Springer International Publishing Switzerland, 2024)
Volume : 225, Article number: 2119